Are institutions informed about news? - Hendershott, Terrence; Livdan, Dmitry; Schürhoff, Norman (Journal of Financial Economics, 2015)
This paper combines daily buy and sell institutional trading volume with all news announcements from Reuters. Using institutional order flow (buy volume minus sell volume) we find a variety of evidence that institutions are informed. Institutional trading volume predicts the occurrence of news announcements. Institutional order flow predicts (i) the sentiment of the news; (ii) the stock market reaction on news announcement days; (iii) the stock market reaction on crisis news days; and (iv) earnings announcement surprises. These results suggest that significant price discovery related to news stories occurs through institutional trading prior to the news announcement date.